ANALISIS YURIDIS ATAS PERMOHONAN ADA ATAU TIDAKNYA PENYALAHGUNAAN WEWENANG BERDASARKAN UNDANG-UNDANG NO. 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN TERHADAP PROSES PERADILAN PIDANA KORUPSI - Mathilda Chrystina Katarina; Syafruddin Kalo; Muhammad Hamdan; Faisal Akbar Nasution (USU LAW JOURNAL, 2018)
ABSTRACT The development of its administrative HR law between State and criminal law entered into a "gray area" giving rise to debate ebelitas among legal experts. How not to, a decision State officials well in order "beleid" nor "diskresi" became the arena of academic studies for was made the base an pemidanaan justification or denial, but on the other hand diskresi without based on legislation give rise to an abuse of authority. By the existence of article 20 and article 21 of ACT No. 30 of 2014 about government administration, opening up space for the internal auditing of the Government Apparatus (APIP) to supervise the prohibition of abuse of authority and PTUN to check and decide there is or none of the elements of abuse of authority, as may be made by the Court of abusing authority in testing TIPIKOR article 3 of ACT PTPK. The results showed that according to the theory of the point of tangent equation, there are administrative law and criminal law related to abuse of authority, including the use of the term Equation 1) 2) Equation, Equation 3) understanding the subject of the norm i.e. Government officials, 4) equation of norgeddrag, i.e. the forbidden deeds (verbod). The close relationship of law and the administration of criminal law that raises the legal experts among the pros cons when APIP inspection results and/or Verdict PTUN stating there are no elements of abuse of authority committed government officials, whether binding the process of criminal justice. Meanwhile, other legal experts have different opinions that the Government officials are convicted could do if the deed Tipikor against criminal law, which preceded and followed the evil inner attitude (mensrea) and result in the loss finances of the State, but in addition to the second opinion there is another legal experts who argued that there are no conflicts of norms, because good PTUN nor the District Court (Criminal/Tipikor) runs the function of each. Parameter test of legality PTUN decisions and/or actions of government officials is legislation (written) and the General principles of good governance/AUPB (not written), while Court TIPIKOR based solely on regulation in writing only. In administrative law distinguished between personal responsibility and position responsibilities. Responsibilities of the position with regard to the legality of the (validity) or defects regarding the juridical authority, procedures, and the substances while personal responsibility with regards to the functionaries or approach the approach behavior, maladministrasi. Criminal responsibility is personal responsibility in the context of losses of State accompanied by malicious intent to benefit yourself.   Keywords: abuse of Authority, law Adminintrasi, and criminal law.